Towards understanding disparities in cancer outcomes for Aboriginal Australians: exploring Aboriginal perceptions and experiences of cancer in Western Australia - Shahid, Shaouli (Curtin University, 2010)
Cancer has become one of the major chronic diseases among Aboriginal and Torres Strait Islander people of Australia, and was declared a health priority in the National Aboriginal and Torres Strait Islander Health Strategy in 2001. Since then efforts have been instigated to improve the epidemiological information with regard to cancer among Aboriginal Australians in several jurisdictions. Specific issues related to cancer have been identified. Aboriginal Australians compared with non-Aboriginal people have higher occurrence of preventable cancers and are less likely to access cancer screening, are diagnosed at a more advanced stage, have poor continuity of care, lower compliance with treatment and lower five-year survival rates. Several risk factors for higher incidence of some cancers have also been noted. However, these do not adequately explain the reasons behind the delayed presentation, poor compliance and different treatment outcomes of cancer among Aboriginal Australians compared to the total population.To investigate and explore the variations in Aboriginal Australians’ beliefs, understanding and perceptions around cancer and their experiences with cancer services, an exploratory, in-depth qualitative study was undertaken in several locations of Western Australia (WA). This was done with a view to understanding Aboriginal decision-making processes in relation to accessing cancer care in WA. The study was approved by the Human Research Ethics Committee (HREC) of Curtin University, the Western Australian Aboriginal Health Information and Ethics Committee (WAAHIEC), the Royal Perth and Sir Charles Gairdner Hospitals, and by the local Aboriginal Community Controlled Health Services (ACCHS) in regions where the research was conducted.The study adopted a hermeneutic phenomenological research design and used qualitative methods. A hermeneutic phenomenological approach was chosen as this allowed understanding to emerge from the experiences of the participants through interpreting the situated meaning of humans in the world. The views of 30 Aboriginal participants – including patients, survivors and close family members who had lost someone to cancer in their families – were gathered through in-depth interviews. The fieldwork was conducted between March 2006 and September 2007. Interview data were tape-recorded, transcribed and analysed using NVivo7 Software. Thematic analysis was carried out from the information.The findings from the study suggest that many factors affect Aboriginal people’s willingness and ability to participate in cancer-related screening and treatment services. Late diagnoses were not only due to late presentations, as some delayed diagnoses occurred in patients who had regular contact with medical services. Participation in treatment is affected by beliefs and fatalistic attitudes towards cancer; limited understanding of the biomedical aspects of cancer and treatment processes; preference of Aboriginal people to use other approaches to healing such as traditional healers and bush medicine; unwillingness to be separated from family and country, and several infrastructural and logistical issues such as cost, transport and accommodation. It was found that fear of death, shame, beliefs such as cancer is contagious and other spiritual issues affected Aboriginal people’s decisions around accessing services.Moreover, miscommunication between Aboriginal patients and health care providers, lack of cultural security and culturally appropriate support services, lack of Aboriginal staff within the hospital to personally support Aboriginal patients, and the alienating environment of oncology treatment services were also mentioned as barriers. Factors important for effective patient-provider communication such as language, shared understanding, knowledge and use of medical terminology require particular attention. Lack of a reliable and on-going relationship with service providers also came up quite persistently. All of these issues were underpinned by the historical context which includes past discriminatory treatment and experiences of racism by Aboriginal people within mainstream medical institutions. These factors contribute to fear of the medical system, feelings of disempowerment, and mistrust towards the system which constrain Aboriginal participation in cancer treatment and other support services.The results of this study indicate that an understanding of the complex “layers” (from micro to macro) of factors and the interactions between them is required to elucidate Aboriginal people’s decision-making processes around engaging and participating in mainstream cancer services. This research identified gaps in knowledge and understanding and a lack of support services within Aboriginal communities.The findings from the research have been shared with relevant cancer-specific and Aboriginal Community Controlled Health Services with a vision to utilise the study outcomes for the benefit of Aboriginal individuals and communities. Aboriginal people were invited to be co-presenters and co-authors wherever the study findings were presented. An Indigenous Women’s Cancer Support Group (IWCSG) was established in Geraldton after the completion of fieldwork there. This support group has been working to raise awareness of cancer in local Aboriginal people.Some suggestions and recommendations to improve services and cancer outcomes for Aboriginal Australians came out of the study. These include: employment of Aboriginal staff in services and involvement of them in decision-making, maintenance of culturally sensitive, empathetic person-to-person contact, provision of infrastructural and institutional support to involve Aboriginal families within the treatment domain; acknowledgement of holistic concepts of health and well-being; and increase Aboriginal health literacy with regard to cancer.